Synthesis and Characterization of NiO/ZnO Nanocomposite and its Application in Ibuprofen Drug Delivery - Mehdi Hossienzadeh; Akbar Hassanpour; Mohamad AliHosseini; Hossein Safardoust; Morteza Mirzaei (شیمی کاربردی روز)
The objective of this research was to explore targeted drug delivery of ibuprofen, a nonsteroidal anti-inflammatory drug, in order to minimize its side effects for patients requiring long-term and continuous use. To achieve this, a ZnO/NiO nanocomposite was synthesized as a carrier for the drug using a simple co-precipitation method. The structural and morphological properties of the nanocomposite were analyzed using XRD, SEM, and EDS techniques, revealing an average diameter of approximately 65 nm. Subsequently, ibuprofen was successfully loaded onto the nanocomposite with the assistance of mint extract as a covering agent. The presence of ibuprofen in the prepared drug-composite sample was confirmed by FT-IR analysis. In vitro investigations were conducted to determine the release of the loaded drug from the brush nanocomposite, which was found to be 20.4%. This research introduces a new green nanostructure in the drug delivery process.